Applying precision nutrition to university students: Insights into their diet quality - Teh, Arnida Hani; Azman, Wan Nur Amirah Wan (World Nutrition Journal, 2025)
Previous studies indicated a rising number of university students affected by malnutrition, primarily due to poor diet quality. Considering the growing emphasis on precision nutrition as a strategy to address diverse health needs This study was conducted to assess the eating patterns, evaluate the quality of diets, and determine the association between diet quality and socioeconomic characteristics among students at Universiti Kebangsaan Malaysia (UKM).